PERSPEKTIF PEREMPUAN (BARAT) TENTANG PERKAWINAN CAMPURAN, POLIGAMI, DAN ISLAM, DALAM NOVEL DEUXIÃˆME FEMME KARYA CAROLINE POCHON - Intan, Tania (ATAVISME, 2019)
The purpose of this study is to examine the perspective of the narrator, French female character, about the phenomenon of mixed marriage, polygamy, and Islam, which is contained in the Deuxième Femme novel 'Second Woman' by Caroline Pochon. To examine these matters, this study uses descriptive analysis methods with criticisms of feminist literature and theories of narotology, cross-culture, and identity. A structural approach is used to analyze the narrative structure that builds the narrator's frame of mind. The results of the study show that (1) mixed marriages conducted by prominent French female figure with male Senegalese figure are not going well because of the imbalance of roles between the two. (2) As part of local culture, polygamy is carried out openly by man with permission from the first wife, but there are elements of compulsion, financial exploitation, and manipulation through patriarchal construction. (3) According to the narrator, men (Senegal) use Islamic teachings as an excuse to commit polygamy and other matters for their interests, and (4) identity retention is important for French female character to maintain her mental stability.